Flipping Out(ward): Changing the Instructional Model for Large-Enrollment Courses - Pitts, Joelle; Fritch, Melia E. (American Library Association, 2017)
For years, Kansas State University Libraries taught face-to-face library instruction sessions for the general education courses, Expository Writing and Public Speaking. We called these Library Days, as they were scheduled daily over week-long periods due to the large number of sections. Expository Writing Library Days were four days of back-to-back, lecture-style sessions for around 1,100 students. It took two weeks to schedule the fifty sections of the course and the eleven librarians needed to lead the instruction and separately operate the computer for each section. The sessions needed to be organized to cover each different research paper assignment and required additional PowerPoint presentations in case the Internet crashed during a session. This was in addition to creating the instruction outlines for all the librarians to follow so each and every student saw the same material, no matter which session they attended. Each session was fifty minutes with approximately seventy students. By the end of the week, we could only hope that the students retained at least ten minutes of our material. This is how we spent a significant amount of library staff time prior to embarking on wide-scale, flipped-classroom implementation that not only transformed how we taught large-enrollment classes, but provided an avenue for improved student learning and self-service. This chapter will cover the design iterations of the online component and discuss the rapid prototyping process utilized to design and implement the program. Assessment and logistics will also be discussed, as will lessons learned and design specifications to consider when embarking on a project of this scale. In essence, we’ll describe how K-State Libraries went from flipping out during Library Days to flipping out(ward) using an effective flipped-classroom model.
Citation: Citation: Pitts, J., Fritch, M. (2017) Flipping Out(ward): Changing the Instructional Model for Large-Enrollment Courses. Creative Instructional Design: Practical Applications for Librarians. p.227-242
Keywords: Large-Enrollment Courses; Instructional Design; Library Instruction; Kansas State University